UPAYA PENINGKATAN PENGETAHUAN DAN KETERAMPILAN WALI SISWA TAMAN KANAK-KANAK (TK) DI BANYUMAS DALAM PENANGANAN PENYAKIT INFEKSI SALURAN PERNAPASAN AKUT (ISPA) : UPAYA PENINGKATAN PENGETAHUAN DAN KETERAMPILAN WALI SISWA TAMAN KANAK-KANAK (TK) DI BANYUMAS DALAM PENANGANAN PENYAKIT INFEKSI SALURAN PERNAPASAN AKUT (ISPA) (STIKes Mitra Keluarga, 2022)
Acute respiratory tract infection (ARI) is one of the infectious disease that is the main cause of morbidity and mortality in the world. ARI is the main cause of infant and under-five mortality. Parents knowledge and skills play an important role in handling ARI in toddlers. The purpose of this community service is to increase the knowledge and skills of parents about acute respiratory infections (ARI) in children and how to handle them. Community service is carried out in August-September 2020 with the target of guardians of the Aisyiyah Bustanul Atfal Kindegarten students in Banyumas. The methods used is interactive lectures and discussions to increase knowledge, while to improve skills by simulating cases in small groups. The knowledge of Kindegarten parents in dealing with ARI has increased, as evidenced by the increased in the questionnaire scores, from 77.5 to 90.8. Guardian skills improve after case simulation